The Ras Target AF-6 is a Substrate of the Fam Deubiquitinating Enzyme - Taya, Shinichiro (The Rockefeller University Press, 1998)
The Ras target AF-6 has been shown to serve as one of the peripheral components of cell–cell adhesions, and is thought to participate in cell–cell adhesion regulation downstream of Ras. We here purified an AF-6-interacting protein with a molecular mass of ∼220 kD (p220) to investigate the function of AF-6 at cell–cell adhesions. The peptide sequences of p220 were identical to the amino acid sequences of mouse Fam. Fam is homologous to a deubiquitinating enzyme in Drosophila, the product of the fat facets gene. Recent genetic analyses indicate that the deubiquitinating activity of the fat facets product plays a critical role in controlling the cell fate. We found that Fam accumulated at the cell–cell contact sites of MDCKII cells, but not at free ends of plasma membranes. Fam was partially colocalized with AF-6 and interacted with AF-6 in vivo and in vitro. We also showed that AF-6 was ubiquitinated in intact cells, and that Fam prevented the ubiquitination of AF-6.